Law on Prevention and Control of Infectious Diseases - The National Assembly (2007)
This Law provides for prevention and control of infectious diseases; border quarantine; epidemic combat; and conditions to assure the prevention and control of infectious diseases in humans. The prevention and control of human immunodeficiency virus (HIV/AIDS) are not governed by this Law. This Law applies to domestic and foreign agencies, organizations and individuals in Vietnam